Enhancing Vocabulary Acquisition through Local Wisdom-Based Diorama Media: A Quasi Experimental Study in Indonesian Primary EFL Education - Matius Tandikombong; Judith Ratu Tandi Arrang; Nehru P. Pongsapan (Eduvelop: Journal of English Education and Development, 2026)
Vocabulary mastery remains a major challenge in English as a Foreign Language (EFL) instruction at the primary school level, particularly when learning materials lack meaningful cultural relevance. This study investigates the effectiveness of local wisdom-based diorama media in enhancing vocabulary acquisition while promoting culturally contextualized learning experiences among young Indonesian learners. A quasi-experimental design was employed involving 36 fifth-grade students from SDN 7 Sesean, North Toraja, who were assigned to experimental and control groups. The experimental group received eight instructional sessions using diorama media representing local cultural heritage, whereas the control group received conventional vocabulary instruction. Data were collected through pre- and post-tests and analyzed using descriptive statistics, tests of normality and homogeneity, and an independent-samples t-test. The findings reveal a statistically significant improvement in vocabulary achievement among students exposed to local wisdom-based diorama media (p < .001), with a mean difference of 20.278 points compared with the control group. These findings indicate that integrating culturally relevant visual media enhances vocabulary acquisition by providing meaningful contextual learning, increasing learner engagement, and strengthening connections between language learning and students' sociocultural experiences. Beyond improving vocabulary outcomes, this study contributes to the growing discourse on culturally responsive pedagogy by demonstrating how local cultural resources can function as pedagogical assets in EFL classrooms. The findings offer practical implications for curriculum developers, English teachers, and policymakers seeking to design culturally sustainable English language instruction in multilingual and multicultural educational settings.